2014
DOI: 10.1016/j.bbcan.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-induced perturbations of cytokines and immune cell networks

Abstract: Until recently, the intrinsically high level of cross-talk between immune cells, the complexity of immune cell development, and the pleiotropic nature of cytokine signaling have hampered progress in understanding the mechanisms of immunosuppression by which tumor cells circumvent native and adaptive immune responses. One technology that has helped to shed light on this complex signaling network is the cytokine antibody array, which facilitates simultaneous screening of dozens to hundreds of secreted signal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
281
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(303 citation statements)
references
References 151 publications
10
281
0
12
Order By: Relevance
“…CXCL10 has been shown to be produced by M1 cells. 7 Our data supported this report (Supplementary Figure 2); however, it remains to be further studied whether M1 cells actually secrete such functional chemokines. If this is the case, M1 cells could help convert prostate cancer from the prototypical cold tumor into a T cell inflamed tumor.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…CXCL10 has been shown to be produced by M1 cells. 7 Our data supported this report (Supplementary Figure 2); however, it remains to be further studied whether M1 cells actually secrete such functional chemokines. If this is the case, M1 cells could help convert prostate cancer from the prototypical cold tumor into a T cell inflamed tumor.…”
Section: Discussionsupporting
confidence: 89%
“…M1 macrophages have been reported to produce CXCL10. 7 In keeping with this, the expression levels of genes associated with M1 macrophages (CD68, CD80 and CD86) were significantly correlated with CXCL10 gene expression (Supplemental Figure 2).
10.1080/2162402X.2018.1486953-F0002Figure 2.Intratumoral chemokine expression after sipuleucel-T treatment (n = 14). (A) Differential expression of immune-related genes in high vs. low CD8 T cell infiltrated cases are shown.
…”
Section: Resultssupporting
confidence: 63%
“…These include elevated expression of the antiphagocytic signals CD200 and CD47 which have been associated with tumor progression and poor clinical outcome in several solid tumor types [81]. Secretion of immunosuppressive cytokines such as TGFβ, IL-10 and Fas-L within the tumor microenvironment can promote the expansion of Tregs and decrease the activation of cytotoxic T cells and NK cells [74]. Tumor cell secretion of indoleamine 2,3-dioxygenase (IDO) and galectins can impair antitumor T cell responses [74].…”
Section: Other Candidate Mechanisms Of Immune Evasionmentioning
confidence: 99%
“…However, in the setting of cancer they are generally thought to be tumor promoting [73,74]. It has been shown that high percentages of CD25+FOXP3+ T cells infiltrate MCC tumors relative to normal skin (Figure 2: process 'F') [70].…”
Section: T Regulatory Cellsmentioning
confidence: 99%
See 1 more Smart Citation